Understanding the biosynthesis of platelets‐derived extracellular vesicles. Issue 3 (16th June 2015) - Antwi‐Baffour, Samuel; Adjei, Jonathan; Aryeh, Claudia; Kyeremeh, Ransford; Kyei, Foster; Seidu, Mahmood A.
Abstract Platelet‐derived extracellular vesicles (PEVs) are described as sub‐cellular vesicles released into circulation upon platelets shear stress, activation, injury, or apoptosis. They are considered as universal biomarkers in a wide range of physiological and pathological processes. They are of tremendous significance for the prediction, diagnosis, and observation of the therapeutic success of many diseases. Understanding their biosynthesis and therefore functional properties would contribute to a better understanding of the pathological mechanisms leading to various diseases in which their levels are raised and they are implicated. The review takes a critical look at the historical background of PEVs, their structural components, the mechanism of their formation, physiological, and exogenous stimuli inducing their release and their detection. It concludes by highlighting on the importance of undertaking in‐depth studies into PEVs biosynthesis and subsequently gaining a better understanding of their biological role in general.